Cause-specific mortality in old age in relation to body mass index in middle age and in old age: follow-up of the Whitehall cohort of male civil servants. - Breeze, E; Clarke, R; Shipley, M; Marmot, MG; Fletcher, A (2006)
BACKGROUND: The relevance of body mass index (BMI) to cause-specific mortality in old age is uncertain. OBJECTIVES: To examine cause-specific 5 year mortality in old age by BMI in old age and middle age (40-69 years). METHODS: Cox proportional hazards for mortality rates among 4862 former male civil servants in relation to quartiles of BMI measured when screened in 1968-70 and when resurveyed in 1997-98 (median age 76 years). RESULTS: The association between all-cause mortality after resurvey and BMI in old age was U-shaped with hazard ratios (HRs) of 1.3 (95% CI 1.1-1.5) for the lightest and heaviest categories relative to the middle two. Among 'healthy' men the lightest (<22.7 kg/m2) had greatest all-cause mortality. The heaviest men (>26.6 kg/m2) had increased risk of cardiovascular disease (CVD) mortality in the first two years or for the whole period if never-smokers. Respiratory mortality was inversely associated with BMI in old age [adjusted HR for trend per BMI category increase 0.6 (0.5-0.7)] but cancer mortality lacked a clear pattern. Net gain or loss of 10 kg or more between middle and old age was a strong predictor of all-cause and CVD mortality. CONCLUSIONS: The shape of the association between BMI in old age and mortality differs by cause of death. Major weight change over time is a warning signal for higher CVD mortality. Having BMI<22.7 kg/m2 in old age is associated with above-average mortality rates even if apparently healthy.